Effects of the green view index on anxiety reduction and perceived exertion during cycling in older adults - Tsai-Chiao Wang; Ta-Wei Tang; Shang-Min Ma; Tsu-Kung Lin; Chia-Liang Tsai (Experimental Gerontology, 2025)
Anxiety is associated with significant functional impairments and diminished mental health and quality of life in older adults. According to stress reduction theory, engaging in physical activity in natural settings may play a critical role in alleviating anxiety among older populations. This study aimed to examine the effects of green exercise under different levels of green view index (GVI) on older adults' psychophysiological responses, including pupil size, anxiety, perceived exertion, and environmental preference. A total of 90 older adults aged 50–75 years were recruited and successfully completed the experiment. Participants were assigned to one of three natural cycling environments, each defined by a different level of GVI: high (60 %), medium (35 %), and low (0 %, control group). The selected environment was a tree-lined path within an urban park featuring lawns, vegetation, and shaded areas. The control group cycled while facing gray urban buildings. All participants completed a single, 20-min moderate-intensity cycling session as the intervention. Pupil size was measured using Tobii Pro Glasses 2, a wearable eye-tracking device operating at 100 Hz. The results showed that the HGVI and MGVI received the smaller pupil size and higher favorable preferences from older adult participants than those from control group. Both excessively high and low levels of GVI in natural environments tend to produce a trade-off between reductions in anxiety and increases in perceived physical exertion. Furthermore, environments with medium to high levels of visible greenery (GVI ≥ 35 %) significantly enhance the psychophysiological benefits of exercise in older adults. Exercise environments with MGVI are considered optimal in balancing anxiety reduction with adequate physical exertion, making them ideal targets for age-friendly urban design.